Retrospective Study of Reported Adverse Events Due to Complementary Health Products in Singapore From 2010 to 2016 - Xu, Yimin; Patel, Dhavalkumar N.; Ng, Suet-Leng P.; Tan, Siew-Har; Toh, Dorothy; Poh, Jalene; Lim, Adena Theen; Chan, Cheng-Leng; Low, Min-Yong; Koh, Hwee-Ling (Frontiers in Medicine, 2018)
The objective of this study is to collate and analyse adverse event reports associated with the use of complementary health products submitted to the Health Sciences Authority (HSA) of Singapore for the period 2010-2016 to identify various trends and signals for pharmacovigilance purposes. A total of 147215 adverse event reports suspected to be associated with pharmaceutical products and complementary health products were received by HSA between 2010 and 2016. Of these, 143191 (97.3%) were associated with chemical drugs, 1807 (1.2%) with vaccines, 1324 (0.9%) with biological drugs (biologics), and 893 (0.6%) with complementary health products. The number of adverse event reports associated with Chinese Proprietary Medicine, other complementary medicine and health supplements are presented. 893 adverse event reports associated with complementary health products in the 7-year period have been successfully collated and analysed. In agreement with other studies, adverse events related to the ‘‘skin and appendages disorders’’ were the most commonly reported. Most of the cases involved dermal allergies (e.g. rashes) associated with the use of glucosamine products and most of the adulterated products were associated with the illegal addition of undeclared drugs for pain relief. Dexamethasone, chlorpheniramine and piroxicam were the most common adulterants detected. Reporting suspected adverse events is strongly encouraged even if the causality is not confirmed because any signs of clustering will allow rapid regulatory actions to be taken. The findings from this study help to create greater awareness on the health risks, albeit low, when consuming complementary health products and dispelling the common misconception that “natural” means “safe”. In particular, healthcare professionals and the general public should be aware of potential adulteration of complementary health products. The analysis of spontaneously reported adverse events is an important surveillance system in monitoring the safety of complementary health products and helps in the understanding of the risk associated with the use of such products. Greater collaboration and communication between healthcare professionals, regulators, patients, manufacturers, researchers and the general public are important to ensure the quality and safety of complementary health products.